Antibacterial Activity of Triterpenoid from The Leaves of Tahi Ayam (Lantana camara Linn) - Kartika MZ; Suryati Suryati; Mai Efdi (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2023)
Tahi Ayam (Lantana camara Linn) is known as the herbal plant to cure several diseases and has been used in folk medicine. The result of this study indicates that the isolated compound and the ethyl acetate fraction are components having antibacterial activity. The isolated compound from the ethyl acetate fraction from the leaves of the Lantana camara Linn plant is 9-hydroxy-Lantadene A. The compound includes the triterpenoid compound group, the molecular formula is C35H52O6, and another name is 22-angeloiloxy-9-hydroxy-3-oxo-olean-12-en-28-oat. The antibacterial activity of this compound was determined by looking at the inhibition zone of the test bacteria, namely Staphylococcus aureus as gram-positive and Escherichia coli as gram-negative. The treatment has been using the disc diffusion method and using amoxicillin as a control positive. The result of the antibacterial activity test revealed that both 9-hydroxy-Lantadene A and the ethyl acetate fraction exhibited antibacterial activity. Becouse there are inhibition zones around the discs at concentrations of 10 μg/disk and 5 μg/disk.